Aflatoxin B1 impairs sperm quality and fertilization competence. (15th January 2018) - Komsky-Elbaz, A.; Saktsier, M.; Roth, Z.
Abstract: Aflatoxins are poisonous byproducts of the soilborne fungus Aspergillus, involved in the decomposition of plant materials. Aflatoxins can be found in various food products, such as maize, sorghum, millet, rice and wheat. AFB1 is the most toxic of these, classified as a carcinogen and mutagen for both humans and animals. AFB1 has been detected in human cord blood and placenta; however, its toxic effect on sperm is less known. The current study examines sperm responses associated with AFB1 exposure. These included acrosome integrity and function, mitochondrial polarity, DNA fragmentation, fertilization competence and early embryonic development. Spermatozoa were obtained from bull ejaculate and epididymis and capacitated in vitro for 4 h with 0, 0.1, 1, 10 and 100 μM AFB1. Following capacitation, acrosome reaction (AR) was induced by Ca 2+ ionophore. The integrity and functionality of sperm were examined simultaneously by florescent staining. A Halosperm DNA fragmentation kit was used to evaluate DNA integrity. An in-vitro culture system was used to evaluate fertilization competence and blastocyst formation rate, using bovine oocytes. Findings indicate dose-responsive variation among compartments to AFB1 exposure. Sperm viability, expressed by integrity of the plasma membrane, was lower in sperm isolated from ejaculate or epididymis after culturing with AFB1. Exposure to AFB1 reduced the proportion of sperm from the epididymis tail undergoing acrosome reaction induced by Ca 2+ ionophore. AFB1 impaired mitochondrial membrane potential (ΔYm) in sperm isolated from ejaculate and the epididymis tail. Exposing ejaculated sperm to AFB1 increased the proportion of sperm with fragmented DNA and reduced the proportion of embryos that cleaved to the 2- to 4-cell stage, 42 h postfertilization, however, the proportion of embryos that developed to blastocysts, 7 days postfertilization, did not differ among groups. The findings explore the harmful effects of AFB1 on sperm viability, ΔΨm and DNA integrity associated with fertility competence. We postulate that AFB1-induced fragmentation in paternal DNA might have a carryover effect on the quality of developing embryos. Further evaluation for the quality of blastocysts derived from sperm exposed to AFB1 is warranted.